1964
DOI: 10.1083/jcb.20.3.377
|View full text |Cite
|
Sign up to set email alerts
|

A Cytochemical Localization of Reductive Sites in a Gram-Negative Bacterium

Abstract: In order to obtain information on the exact location of the respiratory enzyme chain in Gram-negative bacteria, an electron microscopic study was made of the sites of reducing activity of cells that had, in the living state, incorporated tellurite. In the test object Proteus vulgaris, the reduced tellurite was found to be deposited in bodies contiguous with the plasma membrane but different in structure from those described in the Gram-positive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1965
1965
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Bacterial cells resistant to tellurite often turn black when grown in liquid or solid media amended with K 2 TeO 3 , a phenotype that is also displayed by sensitive bacteria growing in media supplemented with sub-lethal concentrations of tellurite [18]. These deposits are of an insoluble material localized to specific subcellular compartments [19], [20], which X-ray diffraction studies have shown to be the less toxic, free metal, tellurium (Te°) [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cells resistant to tellurite often turn black when grown in liquid or solid media amended with K 2 TeO 3 , a phenotype that is also displayed by sensitive bacteria growing in media supplemented with sub-lethal concentrations of tellurite [18]. These deposits are of an insoluble material localized to specific subcellular compartments [19], [20], which X-ray diffraction studies have shown to be the less toxic, free metal, tellurium (Te°) [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of similar experiments concerning dehydrogenase localization have been carried out on bacterial cells (2,6,9,14,15,16,18,19). A relationship between esterases and structures of the bacterial cell has not been studied by electron microscopy.…”
mentioning
confidence: 96%
“…Many microorganisms produce black intracellular deposits when grown in media supplemented with potassium tellurite (14,15,23,25,(28)(29)(30)(31). Even sensitive bacteria are capable of forming jet-black colonies when growing at subinhibitory tellurite concentrations (25).…”
mentioning
confidence: 99%